Analisis Pengaruh Evaluasi Merek, Kepuasan Pelanggan Dan Kepercayaan Merek Terhadap Loyalitas Merek Yang Dimediasi Hubungan Merek (Studi Pada Konsumen Produk Kosmetik Wardah) - Sari, Indah Permata; , Soepatini, S.E., M.Si., Ph.D (2017)
The purpose of this study was to examine the variables that influence consumer brand loyalty in cosmetic products Wardah. This study uses a quantitative approach with descriptive methods. The sampling technique used in this study was a non-probability sampling (sampling technique by not giving a chance to the elements of the population to be sampled) with the type of purposive sampling is a sampling technique that is based on specific criteria on respondents. Based on sampling methods and techniques acquired by 100 respondents who fit the criteria. The data were collected using a questionnaire, after the data is collected and then analyzed using multiple linear regression analysis. The results showed that the evaluation of brand and brand trust has no significant effect on brand loyalty Wardah cosmetics. In contrast to customer satisfaction and brand relationships, the results showed that these variables have a significant effect on brand loyalty Wardah cosmetics. As well as the brand relationship mediate evaluation of brand and customer satisfaction. While the brand does not mediate the relationship of trust brands.